Preparation, stability and wettability of nanofluid: a review - Wahaizad, Safiei; M. M., Rahman; A. R., Yusoff; M. R., Radin (Faculty Mechanical Engineering, UMP, 2020)
Nanofluids possess many advantages over conventional working fluid especially in physical, thermal and rheology properties. Nowadays, nanofluids have been applied extensively in many engineering applications in enhancing the overall performance. Preparation and characterization of nanofluids are vital as the nanomaterials have significant effects on the dispersion and stability of nanofluids. On the other hand, there is a trend to employ more than a single nanoparticle for preparing nanofluid. The hybrid nanofluid receives wide attention due to its capability in improving the thermal-physical properties of single phase nanofluids. In this paper, the flow of formulating nanofluid from preparation method, characterization, wettability analysis and stability techniques are discussed comprehensively. Furthermore, the challenges for obtaining stable suspension and wettability behaviour of nanofluids are discussed as well. The main objective when preparing the nanofluids is to obtain a well-dispersed nanoparticle into the base fluid. Based on the literature review, the impact of surfactant on the stability and the correlation between nanofluids wettability and thermal-physical properties of nanofluids have great potential to discover. There are some aspects that can be considered to expand the knowledge of nanofluids such as the composition ratio of hybrid nanofluid with regards to achieving the best stability and wettability study of hybrid nanofluid with and without surfactant in the suspension. Therefore, a lot of research should be conducted in order to explore the behaviour of nanofluid and the effect of various surfactants in terms of stability as well as its thermal and viscosity effect on the engineering applications.